4. Dr Charles Longley, Bishop of Ripon. (2nd April 2016) - Wilks, Brian
Abstract : Dr Charles Longley, Bishop of Ripon, stayed at the Haworth Parsonage in 1853. A recently discovered letter in from the Bishop to his wife in the Lambeth Palace Archives gives an account of his stay and of his favourable impression of Charlotte. Also included is a poignant letter from Patrick Brontë written after the death of Charlotte two years after.